(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
In modern dentistry, despite the use of various methods of prevention and treatment of caries of dental hard tissues, it remains one of the most common diseases of dental hard tissues. There are hundreds of reasons that contribute to the development of caries in milk teeth. The most important of them socio-demographic, biological, dietary, hygienic and nutritional factors. In this case, the occurrence or attenuation of a number of conditions will later determine the early development of caries in children.